Post-disaster housing reconstruction: Perspectives of the NGO and local authorities on delay issues - Khalid, Khairin Norhashidah; Abdul Nifa, Faizatul Akmar; Mohamed Ismail, Risyawati; Chong, Khai Lin (2016)
Post disaster reconstruction is complex, dynamic and chaotic in nature and as such represents many challenges because it is unlike normal construction. However, the time scale of reconstruction is shorter than the normal construction, but it often deals with uncertainties and the scale of the construction activities required is relatively high. After a disaster impacts a country, many governments, institutions and aid organizations cooperate and involved with the reconstruction process. This is seen as a tool for applying policies and programs designed to remedy the weakness in developmental policies, infrastructure and institutional arrangements. This paper reports a part of an on-going research on post-disaster housing reconstruction in Malaysia.An extensive literature review and pilot interviews were undertaken to establish the factors that contribute to the delay in post-disaster reconstruction project. Accordingly, this paper takes the perspective of recovery from non-government organization (NGO) and local authorities which act as providers of social services, builders of infrastructure, regulators of economic activity and managers of the natural environment. As a result, it is important on how those decisions are made, who is involved in the decision-making, and what are the consequences of this decision.